Design educational units according to the Nedham model to learn some basic skills in tennis - Noor Ali Hussain (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Objective: The purpose of this paper is to preparing educational units for some basic tennis skills according to the Nedham model, and identifying the effect of educational design according to the Nedham model in learning some basic tennis skills.